Mapping the Young-Onset Dementia Research in the Asia-Pacific Region: A Scoping Review - Tan, Gia; Cheung, Gary; Loi, Samantha M; Ma'u, Etuini; Le Heron, Campbell; Cations, Monica; Garrett, Nick; Eustace, Megan; Moon, So Young; Kim, Eun-Joo; Ng, Kok Pin; Ng, Adeline SL; et al. (Wiley, 2026)
Young-onset dementia (YOD), with symptom onset before 65, is an area of increasing public health importance. YOD research in Asia-Pacific remains under-represented in the global YOD research landscape. This scoping review aimed to comprehensively map the existing YOD literature from Asia-Pacific and provide an overview of the research topics explored to date. We followed the PRISMA extension for scoping reviews guidelines and searched Scopus and PsycINFO, using predefined search terms, from their inception to December 31, 2024. Empirical studies involving participants with YOD, or family carers of people with YOD, living in Asia-Pacific, were included. 437 publications were identified. Fourteen of the 42 Asia-Pacific countries/territories have published YOD research, with Japan, Australia, South Korea, and China contributing 82.2% of YOD research in the region. The volume of YOD publications in the Asia-Pacific region increased steadily from the early 2010s. Most studies were case reports/series (34.8%) and quantitative (59.2%), with 5.9% using qualitative or mixed-methods. The YOD research landscape is mostly focused on disease biology such as genetics, neuroimaging, and neuropathology. Despite the impacts of YOD on individuals and their families, only 11.4% of publications, mainly from Australia, examined psychosocial impacts and support services. There is a need for research in the Asia-Pacific region to better understand the journey of YOD and to co-create interventions and services that address the needs of those affected. Potential policy implications include explicit inclusion of YOD within national and regional dementia policies, with acknowledgement that psychosocial impacts of YOD are insufficiently addressed by older age-based dementia frameworks.
Keywords: Asia‐Pacific; neuropsychiatry; research; review; young‐onset dementia; 4203 Health Services and Systems; 42 Health Sciences; Neurological; 1103 Clinical Sciences; 1117 Public Health and Health Services; 1701 Psychology; 3202 Clinical sciences; 4206 Public health; 5203 Clinical and health psychology; Humans; Dementia; Age of Onset; Asia; Biomedical Research; Australia; Humans; Dementia; Age of Onset; Biomedical Research; Asia; Australia; Humans; Dementia; Age of Onset; Asia; Biomedical Research; Australia